The Level of Skills of Female Kindergarten Student Teachers in Using Liveworksheets Platform to Design Interactive Worksheets "A Field Study on a Sample of Fourth-Year Students in the Faculty of Education at Tishreen University" (Journal of Hama University, 2024)
The research aims to determine the level of skills of a sample of female kindergarten student in the Faculty of Education at Tishreen University in using Liveworksheets platform to design interactive worksheets from their viewpoint, and to define its relationship with two variables: attending a course in computer use in education, and previous experience in teaching kindergarten children. To achieve the research objectives, a descriptive approach was used, and a skills questionnaire was prepared and distributed to a simple random sample of (245) fourth-year female students. The data was collected and analyzed statistically, and the researcher arrived at the following results:- The level of skills of female kindergarten Student in using Liveworksheets platform to design interactive worksheets is generally low.- Attending a course in computer use in education raises the level of skills of female kindergarten Student in using Liveworksheets platform to design interactive worksheets.- Previous experience in teaching kindergarten children raises the level of skills of female kindergarten Student in using Liveworksheets platform to design interactive worksheets.